Childhood undernutrition inequalities in Empowered Action Group states of India: evidence from NFHS, 2006-2016 - Kumar, Anil; Gulati, Bal Kishan; Kumar, Jeetendra; Sahu, Damodar; Yadav, Rajaram; Pal, Anita; Rao, M. Vishnu Vardhana (International Journal Of Community Medicine And Public Health, 2021)
Background: Child undernutrition is a major public health problem in many low and middle income countries and malnutrition alone accounted for 45% (3 million deaths annually) deaths among under-five children. Malnutrition is the concealed cause of one out of every two such deaths. A study was undertaken to examine the trends, determinants and socioeconomic-related inequalities in childhood undernutrition in empowered action group (EAG) states, India. The secondary data of the two rounds of National Family Health Survey, NFHS-3 (2005-06) and NFHS-4 (2015-16) comprising of 16,802 and 128,400 children aged 0-59 months respectively was analysed. Methods: Non-linear Fairlie decomposition was used to identify and quantify the separate contribution of different socioeconomic characteristics in gap of childhood malnutrion between 2006 and 2016. Results: Results show that the prevalence of undernutrition has decreased in EAG states during the last one decade, but the prevalence of wasting is remained almost same as 10 years back. The decomposition analysis shows that maternal education, household wealth and place of residence were contributing to socioeconomic inequality in childhood undernutrition from 2006 to 2016. Conclusions: There is a need to adopt different strategies of health policy intervention. It is important to have policies towards improving female literacy in the EAG states because maternal education plays a vital role in child health and literacy rate is very low among women in EAG states. The existence of a functional health insurance system and increasing universal coverage are recommended to mitigate child undernutrition, so that the vulnerable and deprived populations who are not able to access health care facilities, can easily access health care services for early detection and treatment of undernutrition without any financial constraint.